2014
DOI: 10.1002/ajh.23860
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment of reticulocytes from whole blood using aqueous multiphase systems of polymers

Abstract: This paper demonstrates the enrichment of reticulocytes by centrifuging whole blood through aqueous multiphase systems (AMPSs)-immiscible phases of solutions of polymers that form step-gradients in density. The interfaces of an AMPS concentrate cells; this concentration facilitates the extraction of blood enriched for reticulocytes. AMPS enrich reticulocytes from blood from both healthy and hemochromatosis donors. Varying the osmolality and density of the phases of AMPS provides different levels of enrichment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
46
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 30 publications
4
46
0
4
Order By: Relevance
“…, with the salt or the polymer. These results are in good agreement with the criteria used by previous authors,[3–6] who suggested that if the aqueous mixtures composed of the solutes A/B, B/C and A/C are able to form ABS, aqueous mixtures composed of A/B/C will result in the formation of three-phase systems. However, and despite the apparent validity of this criterion, its application requires previous knowledge on the pairs of solutes able to form ABS, resulting in a hard and time-consuming procedure.…”
supporting
confidence: 92%
“…, with the salt or the polymer. These results are in good agreement with the criteria used by previous authors,[3–6] who suggested that if the aqueous mixtures composed of the solutes A/B, B/C and A/C are able to form ABS, aqueous mixtures composed of A/B/C will result in the formation of three-phase systems. However, and despite the apparent validity of this criterion, its application requires previous knowledge on the pairs of solutes able to form ABS, resulting in a hard and time-consuming procedure.…”
supporting
confidence: 92%
“…As an example, the aqueous twophase system has been widely used as biocompatible media for separation of biomolecules 14,15 and cells [16][17][18] . Bioengineered extracellular matrixes 19 and porous scaffolds 20 made from aqueous two-phase droplets exhibit enhanced permeability to nutrients and excellent cytocompatibility.…”
Section: Introductionmentioning
confidence: 99%
“…Similar separation systems can also be prepared as multiple step-density gradients (16). These stable systems have been shown to enable the enrichment of desired populations from complex samples based on very small differences in density (17,18). Such an approach could find additional applications in the study of biochemical differences within quiescent cell populations.…”
Section: Resultsmentioning
confidence: 99%